2006
DOI: 10.3386/w11986
|View full text |Cite
|
Sign up to set email alerts
|

The Polarization of the U.S. Labor Market

Abstract: This paper analyzes a marked change in the evolution of the U.S. wage structure over the past fifteen years: divergent trends in upper-tail (90/50) and lower-tail (50/10) wage inequality. We document that wage inequality in the top half of distribution has displayed an unchecked and rather smooth secular rise for the last 25 years (since 1980). Wage inequality in the bottom half of the distribution also grew rapidly from 1979 to 1987, but it has ceased growing (and for some measures actually narrowed) since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
701
5
35

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(793 citation statements)
references
References 10 publications
36
701
5
35
Order By: Relevance
“…The new economy requires an additional set of skills, particularly those related to the use of ICT. Autor, Levy & Murnane (Autor et al, 2003;Levy & Murnane, 2005;Autor, 2010) analyzed a range of labor tasks in the workplace. They found that, commencing in the 1970s, manual tasks in the US economy declined, reflecting the macroeconomic shifts away from manufacturing described by Karmarkar & Apte (Karmarkar & Apte, 2007;Apte et al, 2008).…”
Section: Labor Market Trends: Need For a Different Skill Setmentioning
confidence: 99%
“…The new economy requires an additional set of skills, particularly those related to the use of ICT. Autor, Levy & Murnane (Autor et al, 2003;Levy & Murnane, 2005;Autor, 2010) analyzed a range of labor tasks in the workplace. They found that, commencing in the 1970s, manual tasks in the US economy declined, reflecting the macroeconomic shifts away from manufacturing described by Karmarkar & Apte (Karmarkar & Apte, 2007;Apte et al, 2008).…”
Section: Labor Market Trends: Need For a Different Skill Setmentioning
confidence: 99%
“…This is often used in the job-polarization and wageinequality literature to measure job quality. See for example, Autor, Katz, and Kearney (2006;2008). Refer to the current data section and appendix for further details on the scoring method.…”
Section: Introductionmentioning
confidence: 99%
“…They find that offshoring has a negative effect on the relative demand for employees with upper secondary education (medium-skilled), while having positive or no effects on employees with tertiary (high-skilled) or lower secondary education (lowskilled). Moreover, Acemoglu (1999) and Autor et al (2006Autor et al ( , 2008 provide evidence on employment polarizing into high-wage and low-wage jobs at the expense of middle-wage jobs over the past 15 years. One plausible explanation is that low-skilled employees perform supportive job tasks that are more difficult to offshore, such as maintenance, and have therefore a less elastic labor demand.…”
Section: Hansen Is a Test For Over Identifying Restrictions (Reportedmentioning
confidence: 99%